2023
DOI: 10.1177/21533687231199271
|View full text |Cite
|
Sign up to set email alerts
|

A New Media Frontier, or More of the Same? A Descriptive Analysis of the “Missing White Woman Syndrome” in Top True Crime Podcasts

Danielle C. Slakoff,
Destiny Duran

Abstract: True crime podcasts are a newer addition to the media and true crime landscape, and listenership is steadily growing. While other forms of true crime have been shown to overrepresent harm against White women and children, no study to date has examined whether White missing women/girls are overrepresented in true crime podcasts compared to women/girls of color. In this study, the researchers examined data from four of the top listened-to podcasts in the United States with two goals in mind: (1) to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Narrowly defined gender prototypes can have a range of very real consequences, such as less media attention being directed toward missing women of color versus White women (Slakoff & Fradella, 2019), as well as pressures for women and girls of color to conform to the category prototype (Collins, 1991). The present work suggests that the way that Black girls and women wear their hair may be one salient way that children begin to exclude Black girls and women from their representations of girl- and womanhood.…”
Section: Discussionmentioning
confidence: 99%
“…Narrowly defined gender prototypes can have a range of very real consequences, such as less media attention being directed toward missing women of color versus White women (Slakoff & Fradella, 2019), as well as pressures for women and girls of color to conform to the category prototype (Collins, 1991). The present work suggests that the way that Black girls and women wear their hair may be one salient way that children begin to exclude Black girls and women from their representations of girl- and womanhood.…”
Section: Discussionmentioning
confidence: 99%
“…Solymosi et al (2021) analysed Tweets made by the Greater Manchester Police (England) between the period of 2011 and 2018 in relation to missing women and found that posts about missing white women had the highest average retweets. Social media creators can also play a role in increasing attention for missing women from minority ethnic communities; however, Slakoff and Duran (2023) reported that their analysis of podcast titles and descriptions revealed that white women and girls were overrepresented in episodes about missing women and girls, compared to missing women and girls from minority ethnic groups.…”
Section: The Role Of Social Mediamentioning
confidence: 99%